Análise de necessidades do uso da língua inglesa em contexto profissional: área editorial - Souza, Renato Antonio de (2009)
This research aims at (1) identifying what are the functions performed by publishing professionals, (2) investigating what are the communicative tasks that these professionals perform in English, (3) investigating what are the learning needs of these professionals and (4) identifying which are subsidies for a course design. This study is based on the theoretical concepts of Language for Specific Purposes, according to Hutchinson & Waters (1987), Robinson (1991), Dudley-Evans & St. John (1998) and Long (2005); on the concept of genre, according to Bakhtin (2000); on the concept of task, according to Shehadeh (2005) and the pedagogical proposal for implementing genres in Language for Specific Purposes courses, according to Ramos (2004). The data were obtained by a questionnaire administered to two learners of a private business English course; a semi-structured interview conducted with a representative of a publishing house; analysis of Labor Ministry, Promérito and Publisher´s job descriptions and also calls for jobs in the labor market to positions occupied by students. Needs analysis carried out found out the following results: the professional profiles of those who work in the publishing area; functions performed by them in the area of expertise; communicative tasks performed in English; their learning needs and also subsidies for an English course design. From these results, an outline on a gender-based syllabus and tasks was presented, in accordance with Dudley-Evans & St John´s parameters (1998) and Ramos´ proposal (2004). In this context, this research contributes to Applied Linguistics by mapping language use and needs of the publishing area; Languages for Specific Purposes teacher development, because, in addition to providing theoretical and methodological subsidies that define and characterize the approach, provide relevant information of English language use in researched area and also for providing the teacher-researcher data to reelaborate the business English course in progress